Analysis of the functional traits of Quercus cerris L. seedlings in the Molise region (southern Italy) - Luca Quaranta (Plant Sociology, 2022)
This study deals with the analysis of seedling fitness in three Quercus cerris wood stands, namely Selva di Castiglione (SC), Bosco della Ficora (BF) and Bosco di San Leo (BSL), developed in different lithological and physiographic conditions and subjected to different forestry practices. A phytosociological study was carried out for analysing the coenological features of the forest stands and to classify these latter from a syntaxonomic point of view. The Pignatti-Ellenberg index (PEi) was calculated on the matrix composed of the phytosociological relevés in order to highlight possible ecological differences or gradients among stands. The phenotypic parameters considered were the stem and root length and the leaf area, whereas the plant functional traits (PFTs) were specific leaf area (SLA), leaf dry matter content (LDMC), leaf thickness (Lth) and chlorophyll content (CHL). The results showed that seedlings coming from different sampling sites exhibited similar values in all the phenotypic parameters. Instead, statistically significant differences were observed in the PFTs. The results suggested that the different adaptation strategies implemented by the seedlings are to be related to the physical environment of the sampling sites and to the different forest structures. The Selva di Castiglione forest stand (SC) exhibited better growth conditions for seedlings testified by higher values of SLA and CHL and lower values of LDMC and Lth. These were interpreted as greater investment in carbon production aimed at rapid development and renewal of the seedling rather than carbon storage aimed at ensuring leaf longevity.